Women’s labour force participation and exit decisions in Malaysia / Sharifah Nabilah Syed Salleh - Sharifah Nabilah , Syed Salleh (2021)
Almost one out of every two Malaysian women of working age are not in the labour force. Despite significant improvements in schooling, women’s participation rate is still low in comparison to men, particularly in the Malay heartland states. Moreover, a large proportion of the currently out-of-the-labour-force female population are dropouts. These patterns have motivated our research. The probable reasons for non-participation (including quitting the labour force) are varied and range from social norms and traditional gender roles within marriage to that of the gender wage differential. All of these factors shaping women’s economic status vary considerably by geography. This research utilised a nationally representative survey data, the Malaysian Population and Family Survey (MPFS) 2014, to investigate some of these explanations for limited labour force participation of women. The first objective of this research is to study the size of the gender gap in labour market participation and the role of place of childhood residence, in explaining the labour market participation gap. The probit regression estimation, which includes detailed controls for individual and household characteristics, current location, indirect proxies of care-related factors and place of childhood residence, found a large gender gap in labour market participation, both in rural and urban Malaysia. We also document a large regional variation in conditional estimates of the gender gap. Female labour force participation in economically advanced states are higher compared to Kelantan and Terengganu, the Malay heartland states. However, this gap can also reflect differences in place-specific norms and traditions. But the influence of childhood residence in historically Malay majority states is shown to proxy indirectly for traditional social customs. More specifically, childhood spent in Kelantan and Terengganu was found to be significant and negatively related to women’s participation, whereas it is insignificant for men. At the same time, we show that the influence of childhood residence cannot be explained away by differences in the poverty rate, local labour market wage differentials and other state-specific factors such as share of women in teaching jobs, and Bumiputera population share. The second objective is to estimate the size of the gender gap in wages and to investigate whether the gender wage discrimination explains the participation decisions. The analysis found that women are paid significantly less compared to men of comparable characteristics. The wages gap are significant throughout age groups and schooling levels. Additionally, alongside low participation of women in the labour market, there is also an issue of exits among women from the labour market – which are not well studied. The final objective is to estimate the size of the gender gap in the labour market exit decisions and identify the determinants of women’s labour market exit decisions. Heckman-probit regression was applied to circumvent the problem of sample selection bias. The analysis found a sizeable gender gap in exit decisions from the labour market where women are more likely to exit the labour market. Being married decreased the probability of participation in the labour market for women and increased the likelihood of exits. Furthermore, the number of children also increased the possibility of exit among women. This shows that the priority of the mother changed with the presence of children.